Ethical Leadership and Educational Justice as Predictors of Organizational Effectiveness in Public Secondary Schools in Delta State, Nigeria - Enomah Sylvester; Ikegbusi Njideka Gloria (PT. Pusmedia Group Indonesia, 2026)
This study examined ethical leadership and educational justice as predictors of organizational effectiveness in public secondary schools in Delta State, Nigeria. Three research questions guided the study. A correlational research design was adopted. The population comprised 11,011 teachers in public secondary schools across the 25 Local Government Areas of Delta State, from which a sample of 551 teachers was selected using a multistage sampling procedure. Data were collected using three researcher-developed instruments: the Ethical Leadership Questionnaire (ELQ), the Educational Justice Questionnaire (EJQ), and the Organizational Effectiveness Questionnaire (OEQ). The instruments were validated by experts in Educational Management, Philosophy of Education, and Measurement and Evaluation. Cronbach's alpha reliability coefficients of 0.85, 0.83, and 0.87 were obtained for the ELQ, EJQ, and OEQ, respectively, indicating satisfactory internal consistency. Data were analysed using simple and multiple linear regression analyses. The findings revealed that ethical leadership and educational justice each positively predicted organizational effectiveness in public secondary schools. The findings further showed that ethical leadership and educational justice jointly predicted organizational effectiveness, with educational justice making a stronger contribution to the prediction of organizational effectiveness than ethical leadership. The study concluded that promoting ethical leadership and educational justice is essential for enhancing organizational effectiveness in public secondary schools. The study recommended regular training for principals on ethical leadership, the promotion of fairness and equity in school administration, and the integration of ethical leadership and educational justice into the appointment, evaluation, and professional development of school principals.